1985
DOI: 10.1104/pp.78.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ Antiport in Isolated Tonoplast Vesicles from Storage Tissue of Beta vulgaris

Abstract: The pH-dependent fluorescence quenching of acridine orange was used to study the Na'-and KI-dependent H' fluxes in tonoplast vesicles isolated from storage tissue of red beet and sugar beet (Beta vulgaris L.). The Na'-dependent H' flux across the tonoplast membrane could be resolved into two components: (a) a membrane potential-mediated flux through conductive pathways; and (b) an electroneutral flux which showed Michaelis-Menten kinetics relationship to Na' concentration and was competitively inhibited by ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
173
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(180 citation statements)
references
References 26 publications
6
173
0
1
Order By: Relevance
“…The effect of Na+ on the dissipation of a transmembrane pH gradient was tested in tonoplast vesicles basically as described before (3,5). The addition of tonoplast vesicles equilibrated at pH 5.8 to a pH 8.0 buffer (pH jump) caused quenching of acridine orange fluorescence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of Na+ on the dissipation of a transmembrane pH gradient was tested in tonoplast vesicles basically as described before (3,5). The addition of tonoplast vesicles equilibrated at pH 5.8 to a pH 8.0 buffer (pH jump) caused quenching of acridine orange fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study (3) we characterized a Na+/H+ antiport in tonoplast vesicles isolated from storage tissue of red beet and sugar beet. Since the vacuolar accumulation of sodium is characteristic of salt-tolerant species (7,8) this tonoplast Na+/H+ antiport may be one of the principal physiological factors conferring salt tolerance on the plant.…”
mentioning
confidence: 99%
“…However, a specific demonstration in guard cell opening and closing has not been made in any study of which we are aware. At the tonoplast, vacuolar sequestration of Na + has been attributed to the function of Na + /H + exchangers (NHX; Blumwald and Poole 1985;Apse et al 1999Apse et al , 2003 and both slow-vacuolar (SV) (Hedrich and Neher 1987;Schönknecht et al 2002;Ivashikina and Hedrich 2005) and fast-vacuolar (FV) channels (Isayenkov et al 2010). It has further been suggested that members of the cation exchanger (CAX) family could transport Na + (Luo et al 2005; see also Zhao et al 2008), but, again, none of these candidates is a part of current models of guard cell function.…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…It has been established that nitrate uptake by plants is an active, H + -coupled process facilitated through the highand low-affinity transport systems (HATS and LATS) which could be constitutive or inducible (Glass and Siddiqi 1995;Glass et al 2001Glass et al , 2002Zhao et al 1999;Tischner 2000;Touraine and Gojon 2001;Forde 2002). Also the nitrate influx into vacuole (Blumwald and Poole 1985;Schumaker and Sze 1987;Kabała et al 2003;de Angeli et al 2006;von der Fecht-Bartenbach et al 2010) as well as its efflux out of the plant cell (Segonzac et al 2007;Lin et al 2008) have been shown to be driven by a proton motive force. Active nitrate transport across plant cell membranes has been attributed to three families including the proton-coupled symporters and antiporters belonging to NRT1, NRT2 (Tsay et al 2007) and CLC multigenic families (de Angeli et al 2006Angeli et al , 2009von der Fecht-Bartenbach et al 2010).…”
Section: Introductionmentioning
confidence: 99%